2006
DOI: 10.1073/pnas.0508419103
|View full text |Cite
|
Sign up to set email alerts
|

Progestin is an essential factor for the initiation of the meiosis in spermatogenetic cells of the eel

Abstract: Meiosis is an indispensable process of sexual reproduction. However, detailed information on the regulatory mechanisms that initiate meiosis is not available. Progestins are important steroids regulating final maturation in male and female vertebrates. In male teleosts, it is known that progestin induces spermiation and sperm maturation. However, a role for progestin in early spermatogenesis or meiosis has not yet been described. In this study, we examined the functions of progestin on the initiation of meiosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 35 publications
7
91
0
4
Order By: Relevance
“…In fish, progestin also plays an important role in spermiation and sperm maturation (10). The effects of 17α, 20β-dihydroxy-4-pregnen-3-one (DHP) in the male Japanese eel were found to induce DNA replication in spermatogonia, but prevent DNA replication at the initiation of meiosis (10).…”
Section: Ssh Libraries and Expressed Sequence Tag (Est) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In fish, progestin also plays an important role in spermiation and sperm maturation (10). The effects of 17α, 20β-dihydroxy-4-pregnen-3-one (DHP) in the male Japanese eel were found to induce DNA replication in spermatogonia, but prevent DNA replication at the initiation of meiosis (10).…”
Section: Ssh Libraries and Expressed Sequence Tag (Est) Analysismentioning
confidence: 99%
“…In fish, progestin also plays an important role in spermiation and sperm maturation (10). The effects of 17α, 20β-dihydroxy-4-pregnen-3-one (DHP) in the male Japanese eel were found to induce DNA replication in spermatogonia, but prevent DNA replication at the initiation of meiosis (10). Two totally distinct classes of putative membrane-bound progestin receptors have been reported in vertebrates; progestin membrane receptor component (PGMRC; subtypes 1 and 2) and membrane progestin receptors (mPR; subtypes α, β, γ).…”
Section: Ssh Libraries and Expressed Sequence Tag (Est) Analysismentioning
confidence: 99%
“…We found for example that spermatogonial stem cell renewal is regulated by an estrogen, estradiol-17␤ (E2) (5), that the initiation of spermatogonial proliferation is regulated by an androgen, 11-ketotestosterone (11KT) (3), and that the initiation of meiosis and sperm maturation are regulated by a progestin, 17␣, 20␤-dihydroxy-4-pregnen-3-one (DHP) (6). It is generally accepted that the biological activity of steroid hormones is mediated via changes in the expression of steroid target genes.…”
mentioning
confidence: 99%
“…The important increase in 17,20β-P levels in blood plasma during the whole spermatogenesis and spermiation stages compared to the undetectable levels at the first development stages sustain the idea that this progestin is involved in the regulation of these two stages of testicular development. It is interesting to note that the presence of 17,20β-P has been considered essential at the beginning of the meiosis process in eels (Miura et al, 2006). This suggests that during the phase in which germ cells enter in meiosis some levels of 17,20β-P are needed to sustain the process and could explain the relative high levels observed in M. furnieri during spermatogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…The occurrence of a small peak of 17,20β-P at early phases of testes development and the fact that trout non-flagellated germ cells were able to produce 17,20β-P in vitro when its precursor was added (Vizziano et al, 1996), suggested that early events of germ cell development could be regulated by this progestin. Indeed, 17,20β-P has been proposed as a meiosis regulator in the Japanese eel (Miura et al, 2006) and its effect on the proliferation of early spermatogonia in zebrafish was recently demonstrated (Chen et al, 2013). Moreover, membrane progestin receptors type β (mPRβ) were detected in zebrafish spermatogonia and spermatocytes using immunochemistry analyses (Hanna & Zhu, 2009), while receptors type α (mPRα) were already expressed in the Micropogonias undulatus testes in a stage when only spermatogonia and spermatocytes were present (Tubbs et al, 2010).…”
Section: Introductionmentioning
confidence: 99%